Gender‐Specific Association Between ABCC2 ‐24C>T SNP and Reduction in Triglycerides in Chilean Patients Treated With Atorvastatin. Issue 5 (4th January 2018) - Prado, Yalena; Arencibia, Alberto; Zambrano, Tomás; Salazar, Luis A.
Abstract: Statins are the first‐line therapy prescribed to lower plasma cholesterol levels. Although being safe and showing several beneficial cholesterol‐independent pleiotropic effects, a significant variability regarding statin's therapeutic goals has been abundantly documented, but less understood. We aimed to investigate the influence of the ABCC2 ‐24C>T single nucleotide polymorphism on Chilean hypercholesterolaemic individuals treated for 4 weeks with 10 mg/day atorvastatin. A total of 127 individuals medicated with atorvastatin 10 mg/day/4 weeks were included. Lipid profiles were determined before and after drug administration by conventional assays. Genotyping of the ABCC2 rs717620 SNP (‐24C>T) was performed with TaqMan ® Drug Metabolism Genotyping Assays. As expected, atorvastatin reduced TC, LDL‐C and TG concentrations ( p < 0.05). Also, HDL‐C levels were increased ( p < 0.05). Minor allele frequency for the rs717620 was 0.232. Overall, atorvastatin response was not associated with the ABCC2 rs717620 SNP ( p > 0.05). Nonetheless, in male individuals carrying the ‐24T allele, we observed an attenuated reduction in both TG values and the TG/HDL‐C ratio after 10 mg/day atorvastatin. This study indicates that TG levels and the TG/HDL‐C ratio are affected by the rs717620 SNP in Chilean males but not female individuals after atorvastatin treatment.